Creep Properties of Densified Wood in Bending - Han, Lei; Kutnar, Andreja; Couceiro, José; Sandberg, Dick (Forests, 2022)
Thermo-hydro-mechanical (THM)-densified timber is rarely used in construction, although its mechanical properties are in many cases excellent. The main reason for its rare use is set-recovery, which reduces the degree of densification over time so that the mechanical properties deteriorate. Our knowledge of the long-term creep of densified timber is insufficient and a full understanding of its long-term behaviour is still lacking. The purpose of this study was to examine the behaviour under long-term loading of Scots pine sapwood densified in an open system at 170–200 °C. The influence of the THM densification process on the creep properties was studied on (1) unmodified specimens, (2) THM-densified specimens, (3) THM-densified specimens that had been further thermally treated, and (4) low-molecular-weight phenol-formaldehyde resin-impregnated and THM-densified specimens. All specimens were loaded at 20 ± 2 °C and 65 ± 5% relative humidity for 14 days under 3-point bending at 35% of the short-term ultimate load, and the bending deformation was registered. The THM densification doubled the density, causing a significant increase in the modulus of rupture but no change in the modulus of elasticity, and reduced the equilibrium moisture content and creep compliance. Post-thermal modification and resin impregnation improved the dimensional stability and further reduced the creep compliance in bending. The results demonstrate that THM densification combined with resin-impregnation or thermal modification reduces the creep of Scots pine timber under a long-term bending load in a constant climate. Validerad;2022;Nivå 2;2022-05-16 (joosat); Funder: Republic of Slovenia, European Regional Development Fund, Slovenian Research Agency ARRS (J4-3087); CT WOOD, Luleå University of Technology